2023
DOI: 10.1002/cplu.202200447
|View full text |Cite
|
Sign up to set email alerts
|

Lyotropic Liquid Crystalline Mesophases of Lithium Dihydrogen Phosphate and 10‐Lauryl Ether Stabilized with Water or Phosphoric Acid

Abstract: The molten phase of transition metal and lithium salts self‐assemble with non‐ionic surfactants to form lyotropic liquid crystalline (LLC) mesophases, which are important in the development of gel‐electrolytes and mesoporous materials. Here, we show that LiH2PO4 forms a semi‐stable LLC mesophase with 10‐lauryl ether (C12H25(OCH2CH2)10OH, C12E10), decoded as Li−EO−X (X is LiH2PO4/C12E10 mole ratio and between 2 and 200). The stability of the Li−EO−X phase is improved by increasing salt concentration (X>20) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…One potential alternative to further enhance structure retention and property control is combining ionic liquids (ILs) and surfactants as contemplated due to potentially synergistic solid interactions. ILs constitute a unique class of primarily organic and ionic materials with a melting point below 100 °C . ILs may also self-organize into polar and nonpolar regions similar to more traditional surfactants. This self-organization has been found to enhance the polymerization rate due to the local increase of polymerizable molecules. , Previous studies have shown that numerous factors, including the interaction of template and precursor and chain length, limit this intrinsic self-organization. , Recently, a long chain imidazolium IL has been used as a templating agent to create vertically aligned pores in silica films utilizing electrochemically assisted self-assembly .…”
Section: Introductionmentioning
confidence: 99%
“…One potential alternative to further enhance structure retention and property control is combining ionic liquids (ILs) and surfactants as contemplated due to potentially synergistic solid interactions. ILs constitute a unique class of primarily organic and ionic materials with a melting point below 100 °C . ILs may also self-organize into polar and nonpolar regions similar to more traditional surfactants. This self-organization has been found to enhance the polymerization rate due to the local increase of polymerizable molecules. , Previous studies have shown that numerous factors, including the interaction of template and precursor and chain length, limit this intrinsic self-organization. , Recently, a long chain imidazolium IL has been used as a templating agent to create vertically aligned pores in silica films utilizing electrochemically assisted self-assembly .…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that the synthesis methods for mesoporous silica with various morphologies have been well-established over the years. However, those synthetic approaches are not applicable for the synthesis of m -TMPs and m -TMPPs. The main challenge in metal phosphates and metal pyrophosphates is a fast reaction between the phosphate or pyrophosphate and transition metal ions, which usually leads to large TMP and TMPP particles that cannot be self-assembled into mesostructured/mesoporous TMP and TMPP particles by surfactant assembly, respectively. Use of phosphoric acid (PA) and pyrophosphoric acid (PPA) slows down the polymerization reactions and brings some degree of control on the self-assembly process. , Acids, used in the assembly process, have multiple roles; they are the precursors, mediators, and water carriers to the LLC media. , Therefore, the use of PA or PPA is the key to this process. There are also some other attempts to slow the reaction between the metal and phosphate or pyrophosphate ions by using metal complexes with various ligands, such as nitrilotris­(methylene)­triphosphonic acid, diphosphonic acid with an alky group, and nonpolar solvents. ,,, Recently, we introduced a new synthetic approach that uses the lyotropic liquid crystalline mesophases (LLCM) of the transition metal salt (TMS), lithium salt (LiX), acid (PA), and a combination of salts and PA with nonionic surfactants .…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Acids, used in the assembly process, have multiple roles; they are the precursors, mediators, and water carriers to the LLC media. 23,24 Therefore, the use of PA or PPA is the key to this process. There are also some other attempts to slow the reaction between the metal and phosphate or pyrophosphate ions by using metal complexes with various ligands, such as nitrilotris(methylene)triphosphonic acid, diphosphonic acid with an alky group, and nonpolar solvents.…”
Section: Introductionmentioning
confidence: 99%